Single functional movement screen items as main predictors of injury risk in amateur male soccer players - Kolodziej, M.; Jaitner, T. (German Journal of Exercise and Sport Research, 2018)
The Functional Movement Screen (FMS) has been applied to identify predisposed players, mainly in professional sports, and their injury risk. Empirical evidence on the FMS in amateur soccer is scant. Furthermore, the composite FMS score contains upper, lower, and core-related body items, which might be related differently in soccer-specific injury incidences. The aim of this study was twofold: to investigate the relationship between the composite FMS score and the injury incidence of amateur soccer players and to analyze the contribution of single FMS test items to the injury state. In all, 83 amateur male soccer players (23±4 years old) were evaluated using the FMS prior to the preparation period of the 2016/2017 season. Injuries (lower extremities, non-contact, time loss) were continuously documented throughout the first competition period. The composite FMS score differed significantly (p=0.017) between injured (15.1±2.5) and non-injured (16.5±2) players. A twofold increase in the risk of injury was found for a composite FMS score of 14 or less. Significant correlations between single test items with a score=2 and injured players were found for the trunk stability push-up exercise (2=17.4, df=1, p<0.001, f=0.5) and the rotary stability exercise (2=6.7, df=1, p=0.009, f=0.3). The composite FMS score seems to be an indicator of injury risk in amateur soccer with injured players having lower core stability and lower core strength.